Unusual effect of chemical communication on social aggression in juvenile cichlid fish Cichlasoma paranaense (Cichliformes: Cichlidae) - Santos Gauy, Ana Carolina dos [UNESP]; Bolognesi, Marcela Cesar [UNESP]; Goncalves-de-Freitas, Eliane [UNESP] (Soc Brasileira Ictiologia, 2019)
Some fish species are socially organized and show a social rank order which is achieved through aggressive interactions. After hierarchy is settled, such species communicate their ranks through several sensorial cues; this communication is adaptive because it reduces detrimental effects from physical contests. Cichlid fish are socially organized and signal their social ranks through visual. acoustic and chemical communication. The response to signaling may vary according to the species and environment; the knowledge of different species is fundamental to understand the evolutionary forces upon their social communication. We tested the effect of chemical signaling on social groups of juvenile cichlid Cichlasoma paranaense by renewing the water in the aquarium, a procedure that washes away chemical information and increases aggressive interactions in other cichlid species. Two treatments were designed: 50% and 0% water renewal. Aggressive interactions were video-recorded immediately before water renewal, 1 min, 1 h, 2 h, and 24 h after water renewal. The treatment with the water renewal did not increase aggressive interactions within the group. The 50% water renewal apparently reduced aggressive interactions in this species, indicating an interspecific difference on the aggressive response to chemical variation in the social environment.
Keywords: Agonistic behavior; Social behavior; Social enviromnent; Social signals; Water renewal